Effectiveness Of Portland Cement Type 1 In Stabilizing Soft Clay Soil As Subgrade For Road Construction - Iskandar, Dedi; Putri, Elsa Eka; Hakam, Abdul; Fitri, Arniza (Jurnal Rekayasa Sipil (JRS-Unand), 2023)
Sawah Lunto – Talawi road segment (STA 139 + 700 m) in Sawah Lunto city, West Sumatera province has sustained major damages and been the scene of several accidents since the past few years. The degression of soft clay subgrade, which has a limited bearing capacity and makes it structurally impractical to sustain road construction, was discovered to be the source of these damages. As a recent option for enhancing soil qualities, soil stabilization by employing a variety of pozzolanic and industrial materials has gained popularity. The objective of this study is to investigate the effectiveness of Portland cement type 1 as stabilizing material in improving the soil properties and carrying capacity requirements for soft clay soil used as subgrade in road construction. To accomplish the objectives of this study, a laboratory testing procedure was implemented. Unconfined Compressive Strength (USC) values on natural soil and treated soil with Portland cement type 1 admixture were measured and compared during laboratory experiments. Soft clay soils were stabilized with varying percentages of Portland cement type 1 with the proportions of approximately 1%, 2%, 3%, 4%, 5%, 6%, 7%, and 10% by dry weight of soil during a 7-days curing period. Laboratory testing were performed in compliance with Indonesian National Standard (SNI): SNI 3420-2008 for testing Unconfined Compressive Strength. According to the results of laboratory testing, the UCS values increased roughly from 0.634 kg/cm2 (undisturbed natural soil) to 2.832 kg/cm2 (treated soil) by adding 3% of Portland cement type 1, and up to 8,024 kg/cm2 (treated soil) by adding 10% of Portland cement type 1. Based on the findings, it can be demonstrated that Portland cement type 1 can enhance clay soil's properties used as a subgrade for road construction, can create more stable road conditions, and can ultimately meet the technical feasibility requirements for the subgrade carrying capacity, particularly at the Sawah Lunto - Talawi road segment (STA 139 + 700 m).